The Study of Using Vinegar Acid as a Dangke Coagulant Alternative - Sukasri, Arifah; Utomo, Wahyu Budi; Waryanto, Puput; Syarif, Sahreni; Khair, Nur Irna Rahmadayanti (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Coagulated by papaya sap, dangke is known as a traditional dairy product belonging to the household-scale processing business in Enrekang, South Sulawesi Province, Indonesia. Vinegar is another coagulant that can be used in making dangke. This study aimed to utilize vinegar as an alternative dangke coagulant other than papaya sap, to analyze the texture of dangke, to use different salt concentrations while making dangke with vinegar, to perform proximate tests, and to conduct organoleptic tests. Dangke was made from 1 L cow's milk mixed with 5 mL of vinegar. For roughly 20 minutes, the mixture is cooked at 6570C while being stirred. The curd was separated from the whey and then shaped into dangke. Dangke was then soaked for 75 minutes in varied salt concentrations of 2%, 3%, and 4%. The texture analyzer (softness) result of this dangke was 125.974 g/s. It was close to the texture of traditional dangke. Proximate analyses were performed. The result that comes close to the result of traditional dangke was 3% salt-soaked dangke with a moisture content of 35.82%, an ash content of 1.44%, dissolved protein content of 0.47%, and fat content of 5.06%. An organoleptic test of preference for dangke vinegar was also carried out. The results of this study are expected to be utilized by local industries having difficulties in obtaining papaya sap as a dangke coagulant.